Kompetensi Akuntansi Sumber Daya Manusia dan Kinerja Pegawai dengan Produktivitas sebagai Variabel Intervening - Arsani, Ni Kadek Budi; Rasmini, Ni Ketut (E-Jurnal Akuntansi; Vol 31 No 9 (2021), 2021)
This study aims to determine the effect of human resource accounting competence on employee performance with BUM Desa productivity as an intervening variable. Data collection was done through a questionnaire. This study uses a quantitative approach with primary data sources and secondary data. The population in this study were all BUM Desa in Gianyar Regency. The sample in this research is BUM Desa in Gianyar Regency with purposive sampling method. The analysis technique used is path analysis. The test results show that human resource accounting competence has a positive effect on the productivity of BUM Desa in Gianyar Regency. The productivity of BUM Desa has a positive effect on employee performance at BUM Desa, Gianyar Regency. Human resource accounting competence has a positive effect on employee performance at BUM Desa Gianyar Regency. Human resource accounting competence has a positive effect on employee performance through productivity at BUM Desa, Gianyar Regency. Keywords: Human Resource Accounting Competence; Productivity; Employee Performance.